2016
DOI: 10.1002/ajh.24401
|View full text |Cite
|
Sign up to set email alerts
|

Disease, treatment, and outcome differences between men and women with follicular lymphoma in the United States

Abstract: We aimed to comprehensively study sex differences in disease and patients’ characteristics, treatment and outcomes in patients with follicular lymphoma (FL) in the United States (USA) utilizing the National LymphoCare Study registry (2004–2014). Among evaluable males (n = 1277) and females (n = 1375) with FL, females less commonly received anthracyclines and were more likely to receive rituximab monotherapy. Overall response rates were comparable between sex groups. With a median follow-up of 8.1 years, male s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 19 publications
3
22
2
Order By: Relevance
“…We know that 20% of patients have FL progression within 2 years of the first-line treatment. 21 These results differ from those recently published by Nabhan et al 22 from the LymphoCare study, which found that lymphoma-related mortality (HR, 0.46; 95% CI, 0.23-0.93) and OS (HR, 0.63; 95% CI, 0.41-0.97) favored females who were 60 years old or older. 1 and 2 [see online supporting information]).…”
Section: Discussioncontrasting
confidence: 65%
“…We know that 20% of patients have FL progression within 2 years of the first-line treatment. 21 These results differ from those recently published by Nabhan et al 22 from the LymphoCare study, which found that lymphoma-related mortality (HR, 0.46; 95% CI, 0.23-0.93) and OS (HR, 0.63; 95% CI, 0.41-0.97) favored females who were 60 years old or older. 1 and 2 [see online supporting information]).…”
Section: Discussioncontrasting
confidence: 65%
“…In multivariable analysis, male sex, high FLIPI, low albumin, low absolute monocyte count, and interfollicular CD10 staining were all associated with early POD. The association of male sex with early POD and subsequent worse OS suggests a different biology of follicular lymphoma and different pharmacokinetics of rituximab in males compared to females . Hypoalbuminemia and low absolute monocyte count have been correlated with prognosis in other studies in FL .…”
Section: Discussionmentioning
confidence: 97%
“…Our results are therefore consistent with the NLCS, which recruited patients from 2004 to 2007: US physicians preferred R‐CHOP (55%), followed by R‐CVP (23%), and R‐fludarabine‐based regimens (16%) as first‐line chemoimmunotherapy. Similar to our findings, females less commonly received anthracyclines . However, these comparisons were not corrected for covariates.…”
Section: Discussionmentioning
confidence: 99%